Desynchronization of Circadian Clocks in Cancer: A Metabolic and Epigenetic Connection - Padmanabhan, Kiran; Billaud, Marc (Frontiers in Endocrinology, 2017)
Circadian clocks are innate oscillators that drive daily rhythms in metabolism, physiology and behavior. 24-hour rhythms in gene expression, driven by core-clock transcription factors, reflect the epigenetic state of the cell, which in turn is dictated by the metabolic environment. Cancer cells alter their metabolic state and gene expression and therefore are likely to tweak circadian clock function in their favor. Over the past decade, we have witnessed an extraordinary increase in systems-level studies that suggest intricate mechanistic links between the cellular metabolome and the circadian epigenome. In parallel, reprogramming of cellular clock function in cancers is increasingly evident and the role of clock genes in the development of hematological tumors, as well as their pathophysiological effects on tissues distal to the tumor have been described. Furthermore, the interplay between components of the circadian clock, metabolic enzymes and oncogenes is starting to be better understood, such as the close association between overexpression of the Myc oncogene and perturbation of circadian and metabolic rhythms, thus opening new avenues to treat cancers. This review article explores current knowledge on the circadian metabolome and the molecular pathways they control, with a focus on their involvement in the development of hematopoietic malignancies.